2005
DOI: 10.1007/11527923_62
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the Time-Variant Covariates for Gait Recognition

Abstract: Abstract. This paper deals with a problem of recognition by gait when time-dependent covariates are added, i.e. when 6 months have passed between recording of the gallery and the probe sets. We show how recognition rates fall significantly when data is captured between lengthy time intevals, for static and dynamic gait features. Under the assumption that it is possible to have some subjects from the probe for training and that similar subjects have similar changes in gait over time, a predictive model of chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…In this way the overall CCR could be improved from 23 to 27% [20]. By modelling the change in feature space (by using linear interpolation) the recognition rate with variation in time was improved from 23% to 65% [19]. Both of these are considerably improved over the 3% achieved by Phillips et al [15].…”
Section: Covariate Analysis For Gait Recognitionmentioning
confidence: 95%
See 1 more Smart Citation
“…In this way the overall CCR could be improved from 23 to 27% [20]. By modelling the change in feature space (by using linear interpolation) the recognition rate with variation in time was improved from 23% to 65% [19]. Both of these are considerably improved over the 3% achieved by Phillips et al [15].…”
Section: Covariate Analysis For Gait Recognitionmentioning
confidence: 95%
“…Phillips reported a CCR of 57% for Data (I) with load carriage and footwear covariates whilst a CCR of 3% is achieved for Data (II) with the following covariates : time, footwear, and clothing. Time has been shown [15,19] to play a major part in reducing recognition capability by gait. Using a silhouette based approach Veres showed that this could be redressed by fusing those parts of the gait signature which are invariant with time.…”
Section: Covariate Analysis For Gait Recognitionmentioning
confidence: 99%
“…This is mainly because static features are dependent on clothing, bags, and other factors [12,11] which would certainly affect the recognition performance. On the other hand, Cutting et al [4] argued that dynamic features contribute significantly more in human recognition than static cues such as height.…”
Section: Introductionmentioning
confidence: 99%
“…Bouchrika and Nixon (2008) conducted a comparative study of their influence in gait analysis. Veres et al (2005) proposed a remarkable predictive model of the "time of execution" covariate to improve recognition performance. The issue has however been approached so far on an empirical basis, i.e.…”
Section: Influence Of Covariatesmentioning
confidence: 99%